Water Conditioning Refrigeration System Design and Construction for Lobster Cultivation - Wardika; Yudhy Kurniawan; Hadi Prayitno; Sintya Haula H. (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
This research is to determine the cooling burden of the water conditioning system for lobster conditioning, where water must be conditioned to its temperature by its 21°C conditioning. This device uses steam compression systems precisely by utilizing water conditioning systems to condition water to stay awake at a temperature of 21°C. The method used in this study was to determine the volume of the water tank and its cooling capacity by calculating the load load and calculating the heat load through the walls of the water tank and other heat generated. For lobster cultivation, an air conditioning machine with a capacity of 1/2 PK. From the results of testing the tool for 3 hours, the results of system performance at an evaporation temperature of 15.2 °C and a product temperature of 21 °C obtained a Carnot COP of 7.11, an actual COP of 5.87, and an efficiency of 82.55%. This is in accordance with Design Carnot COP 8, actual COP design of 6.7, and design efficiency of 83%.